Early nCPAP versus intubation in very low birth weight infants - Pedro Neves Tavares; Filipa Flor-de-Lima; Henrique Soares; Hercília Guimarães (Journal of Pediatric and Neonatal Individualized Medicine, 2013)
For many years endotracheal intubation and mechanical ventilation have been the standard of care for very low birth weight infants but, in the last decade, nasal continuous positive airway pressure (nCPAP) has been described in many studies as an option for the treatment of preterm infants with respiratory distress syndrome. In fact, recent studies have shown that early nCPAP is not associated with higher rates of morbidity and mortality and does not imply more days of ventilation support when compared to traditional ventilation techniques. The authors conducted a study to compare the outcomes (in terms of mortality, morbidity and need for medical support) of very low birth weight infants treated with nCPAP or endotracheal intubation and mechanical ventilation. One hundred and four newborns were enrolled in this study, 44 (42.3%) were treated with nCPAP and 60 (57.7%) with endotracheal intubation followed by mechanical ventilation. A subgroup analysis of newborns with gestational age between 28 and 31 weeks was also performed. It included 57 newborns with similar demographic characteristics, 29 (50.9%) treated with nCPAP and 28 (49.1%) with endotracheal intubation followed by mechanical ventilation. No statistically significant differences were found in the frequency of death or bronchopulmonary dysplasia. Statistically significant differences were found in the prevalence of hyaline membrane disease (p = 0.033) and surfactant administration (p = 0.021) with lower rates in the nCPAP group. No other differences were found in the prevalence of other morbidities or in the need for medical support after birth. These results suggests that nCPAP might be chosen as primary ventilatory support choice in very low birth weight preterm, when there are no contraindications to its use.